REFLECTION OF SPIRITUAL AND EDUCATIONAL REFORMS IN THE STATE INNOVATIVE DEVELOPMENT IN NEW UZBEKISTAN (Archive of Conferences, 2021)
The priority mechanisms of the state innovation policy, integrated conceptual theoretical developments, priorities and current tasks of practical proposals and recommendations for their implementation are considered in the process of ensuring spiritual growth. Spirituality is a mirror. In the mirror, a person sees his image.